2021
DOI: 10.1002/chem.202101201
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Improbable Foldamer Shapes with Strained Macrocycles

Abstract: The alkylation of some secondary amide functions with a dimethoxybenzyl (DMB) group in oligomers of 8amino-2-quinolinecarboxylic acid destabilizes the otherwise favored helical conformations, and allows for cyclization to take place. A cyclic hexamer and a cyclic heptamer were produced in this manner. After DMB removal, X-ray crystallography and NMR show that the macrocycles adopt strained conformations that would be improbable in noncyclic species.The high helix folding propensity of the main chain is partly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 69 publications
(51 reference statements)
2
7
0
Order By: Relevance
“…This is the main reason why 3a has better helical selection than 1a . Based on the above discussion, we conclude that the electronic delocalization effect influences the selection of helical handedness, and the delivery of chirality in the conjugated chains is easier than in the unconjugated system, which corresponds to some experimental results [12–15].…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…This is the main reason why 3a has better helical selection than 1a . Based on the above discussion, we conclude that the electronic delocalization effect influences the selection of helical handedness, and the delivery of chirality in the conjugated chains is easier than in the unconjugated system, which corresponds to some experimental results [12–15].…”
Section: Resultssupporting
confidence: 72%
“…This is the main reason why 3a has better helical selection than 1a. Based on the above discussion, we conclude that the electronic delocalization effect influences the selection of helical handedness, and the delivery of chirality in the conjugated chains is easier than in the unconjugated system, which corresponds to some experimental results [12][13][14][15]. From the investigation of foldamers 1, 2, and 3, it is found that three-center hydrogen bonds between the terminal group and oligomers are found in both 2 and 3, but helical selection is better in 3 than in 2.…”
Section: Helix Handedness Of β-Pinene-derived Pyridyl Amine Substitut...supporting
confidence: 70%
“…18). 96 A series of noncyclic precursors 45a–d , 46a and 46b were produced and it was found that macrocyclization failed for those reactants containing a single DMB substituent or two consecutive DMB groups at the end. The remaining precursors could be lead to the corresponding macrocycles 47c , 47d , and 48b in moderate to good yields.…”
Section: Highly Efficient Synthetic Approachesmentioning
confidence: 99%
“…Recently, there have been extensive studies on the construction process and folding behavior of foldamer. [5][6][7][8] Diversified foldamers have been constructed by mimicking the folding behavior of biomolecules, with structural diversity and multiple functionalities. [9][10][11] The folded structures show dynamic property adaptive to the environments and guest molecules, greatly expanding applications in supramolecular chemistry and smart materials.…”
Section: Introductionmentioning
confidence: 99%